(untitled) (Scientia Agropecuaria, 2012)
The white-tailed deer (Odocoileus virginianus peruvianus) is a ruminant of the family Cervidae that is managed as a game species in the Sauce Grande area of Coto de Caza El Angolo (CCEA), Piura, Peru. The aim of this study was to propose a health protocol for the white-tailed deer of CCEA as an essential component of their management work plans as well as to serve as a model for other wildlife in protected natural areas. For the development of this protocol a literature review was done on the species, along with five visits to CCEA for the evaluation of the area and the standardization of some procedures, where biological samples were collected from white-tailed deers and domestic mammals in the area for microbiologic analysis.